Evaluation of the Escherichia coli (E.coli) Strains based on protein profiles obtained from traditional Ice cream in Isfahan City - Maryam Ranjbar; Reza Nedaeinia; Mohammad Goli; Mostafa Manian; Mohammad Reza Meracy; Mansour Feizi; Nafiseh Kargaran (Biological Journal of Microorganism, 2016)
Introduction: Bacterial strains present in food products undergo different thermal processes such as coldness and warmth. Such cases cause a shock in bacteria and force the bacteria to produce proteins and partly, develop a change in the production of enzyme. This can give the strain a special characteristic, knowledge of this characteristic will contribute to a timely and more precise identification.